Length-weight relationship and condition factor of selected small Cyprinid fishes from river Burhi Gandak in North Bihar, India - Sahil; Mogalekar, H.S.; Chandran, Sudhan; Nayak, S.K.; Kumar, Shivendra; Singh, S.K. (Journal of the Inland Fisheries Society of India, 2023)
The present study was conducted in Burhi Gandak River in Bihar to investigate the length-weight relationship and condition factor of four small cyprinids viz. Cirrhinus reba (Hamilton, 1822), Puntius sophore (Hamilton, 1822), Puntius terio(Hamilton, 1822) and Ambylpharyngodon mola (Hamilton, 1822). A total of 677 C. reba, 969 P. sophore, 873 P. terio and 1015 A. mola specimens were collectedusing traditional boats and some locally made nets like Dhoni jaal, Auptha jaal, Chauni jaal and modified traps. The regression equation was found as Log W = -2.036 + 2.97 Log L (r=0.94) for Cirrhinus reba, Log W = -1.962 + 3.14 Log L (r=0.84) for Puntius sophore, Log W = -0.932 + 1.86 Log L (r=0.72) for Puntius terio and Log W = -2.031 + 3.39 Log L (r=0.84) for Ambylpharyngodonmola. The length weight relationship revealed that C. reba follows the isometric growth pattern while P. sophore and A. mola exhibit positive allometric growthpattern and negative growth pattern was observed in P. terio. The variation in condition factor was observed in case of P. terio while the other species are in good condition in this riverine habitat.